Inpatient post-COVID-19 rehabilitation program featuring virtual reality—Preliminary results of randomized controlled trial - Rutkowski, Sebastian; Bogacz, Katarzyna; Rutkowska, Anna; Szczegielniak, Jan; Casaburi, Richard (Frontiers in Public Health, 2023)
Numerous recommendations from pulmonary scientific societies indicate the need to implement rehabilitation programs for patients after COVID-19. The aim of this study was to propose an innovative comprehensive intervention based on a hospital-based pulmonary rehabilitation program for individuals with post-acute sequelae of COVID-19. It was decided to evaluate two forms of hospital rehabilitation: traditional and one provided through virtual reality. Preliminary results are based on a group of 32 patients (20 female and 12 male), of average age 57.8 (4.92) years in the period of 3 to 6 months after the initial infection. Primary outcomes included analysis of lung function, exercise performance and stress level. A 3-week, high-intensity, five-times per week pulmonary rehabilitation program was designed to compare the effectiveness of a traditional form with a VR-led, novel form of therapy. The analysis of the results showed a statistically significant improvement in both groups with regard to exercise performance expressed as 6MWT distance. Moreover, a statistically significant decrease in dyspnoea levels following the 6MWT was also noted in intergroup comparison, but the between-group comparison revealed non-statistically significant changes with low effect size. Regarding lung function, the analysis showed essentially normal lung function at baseline and a non-statistically significant improvement after the completion of the rehabilitation program. The analysis of the stress level showed a statistically significant improvement in both groups within the inter-group comparison, yet the between-group comparison of deltas values showed a nonsignificant difference with low effect size. A 3-weeks inpatients pulmonary rehabilitation program led to improvement of the exercise performance of people with post-acute sequelae of COVID-19 , but not lung function. Furthermore, the program was shown to reduce patients' stress levels. A comparison of the traditional form of rehabilitation to the novel form using VR, shows similar effectiveness in terms of exercise performance and stress levels.